2005
DOI: 10.1097/01.tp.0000158325.12837.a2
|View full text |Cite
|
Sign up to set email alerts
|

Thymoglobulin Versus ATGAM Induction Therapy in Pediatric Kidney Transplant Recipients: A Single-Center Report

Abstract: Thus, Thymoglobulin induction was associated with a decreased incidence of acute rejection and an increased incidence of EBV infection in pediatric KTx recipients. EBV monitoring should be performed in EBV-naive recipients receiving Thymoglobulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…A single retrospective pediatric study demonstrated that muromonab-CD3 (OKT3) and equine antithymocyte globulin (ATG) (ATGAM, Upjohn, USA) were equally effective in reversing CRR [4], though no further comparative studies have been conducted in children. Thymoglobulin, a polyclonal rabbit ATG preparation shown to be associated with fewer episodes of acute rejection than with ATGAM when used as induction therapy, has been the most commonly used antilymphocyte preparation in recent years [5]. Following improvements in immunosuppression protocols over the last decade, there has been a substantial reduction in the incidence of acute allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…A single retrospective pediatric study demonstrated that muromonab-CD3 (OKT3) and equine antithymocyte globulin (ATG) (ATGAM, Upjohn, USA) were equally effective in reversing CRR [4], though no further comparative studies have been conducted in children. Thymoglobulin, a polyclonal rabbit ATG preparation shown to be associated with fewer episodes of acute rejection than with ATGAM when used as induction therapy, has been the most commonly used antilymphocyte preparation in recent years [5]. Following improvements in immunosuppression protocols over the last decade, there has been a substantial reduction in the incidence of acute allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] On the other hand, studies of ATG-F have reported mixed results. 2,16 Notwithstanding these contradictory findings, we could not find significant differences, except for the WBC count at month 1, between the 2 drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Two retrospective studies evaluated the relative efficacy of no induction and induction with rATG, eATG, or basiliximab in pediatric patients also receiving combination immunosuppressive therapy. 35,36 The first of the studies, by Khositseth et al, compared rATG 1.5 mg/kg/day for 10 days with eATG 15 mg/kg/day for 14 days in subjects receiving concomitant corticosteroids, cyclosporine, and mycophenolate mofetil. 36 Khositseth et al found that rATG induction was associated with significantly lower rates of BCAR (33% versus 50%, P=0.02) up to 3 years after transplantation in these patients.…”
Section: Special Populations Pediatric Renal Transplant Recipientsmentioning
confidence: 99%
“…35,36 The first of the studies, by Khositseth et al, compared rATG 1.5 mg/kg/day for 10 days with eATG 15 mg/kg/day for 14 days in subjects receiving concomitant corticosteroids, cyclosporine, and mycophenolate mofetil. 36 Khositseth et al found that rATG induction was associated with significantly lower rates of BCAR (33% versus 50%, P=0.02) up to 3 years after transplantation in these patients. Median time to BCAR and severity of BCAR were not significant between the treatment groups, …”
Section: Special Populations Pediatric Renal Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation